The Effect Of Career Development And Work Lıfe Balance Toward Intentıon To Stay On Generatıon Z In Bandung Raya - Putri Azzahra Febriyanthy; Fetty Poerwita Sary (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The purpose of this study is to examine the relationship between career development and intention to stay in Generation Z in the Bandung Raya area, and the relationship between work life balance and intention to stay in Generation Z in the Bandung Raya area. The study used a quantitative research method. The population of the study was Generation Z in the Bandung Raya area, with a sample size of 150 respondents. Non-probability sampling with purposive sampling was used to select the sample. Descriptive analysis and structural equation modeling-partial least squares (SEM-PLS) analysis were used to analyze the data. The results of the study showed that career development has a significant and positive effect on intention to stay. Work life balance also has a positive effect on intention to stay. In other words, the better the career development and work life balance in a company, the higher the intention to stay or the desire of Generation Z employees to stay with the company.